Topical ruxolitinib 1.5% (JAK1/JAK2 inhibitor) improves clinical and patient‐reported outcomes in moderate to severe chronic hand dermatitis: Data from a small open‐label trial - Hannah D. Smith; Jag S. Lally; Alison Moy; Julie Ryan‐Wolf; Anna De Benedetto (Wiley, 2024)
Abstract Background Chronic hand dermatitis (CHD) has suboptimal treatments and a negative impact on quality of life (QoL). Topical ruxolitinib, a JAK1/JAK2 inhibitor, is approved for vitiligo and mild‐to‐moderate atopic dermatitis, but has not previously been studied specifically for CHD. Objectives Evaluate the impact of ruxolitinib in CHD. Methods A 12‐week, investigator‐initiated, open‐label trial evaluated ruxolitinib 1.5% in 15 adults with recalcitrant moderate‐to‐severe CHD. Primary outcomes included the proportion of patients: (1) achieving an Investigator Global Assessment (IGA) treatment success (0 or 1 score with a two‐step improvement) (2) a Hand Eczema Severity Index (HECSI)‐75 improvement at 12 weeks. Additional outcomes: clinical improvement at 4 and 8 weeks, improvement in itch (Numerical Rating Scale [NRS]) and QoL outcomes (i.e., Dermatology Life Quality Index [DLQI] and Skindex‐Mini). Results At 12 weeks, 13/15 participants (86%) achieved a HECSI‐75, 12/15 participants (80%) had a two‐point reduction in IGA and 8/15 participants (53%) achieved an IGA treatment success. Both atopic dermatitis (AD; n = 7) and non‐AD (n = 8) CHD participants had clinical improvement in HECSI at 12 weeks (p < 0.01). 10/12 participants with baseline NRS ≥ 2 (83%) achieved a ≥ 2 point reduction on average itch at 12 weeks. 9/10 with baseline NRS ≥ 4 (90%) achieved a ≥4‐point itch reduction by 4 and 12 weeks. A significant decline in self‐reported daily itch (average and worst) was observed within the first week of treatment (p < 0.001). By CHD subtype, AD‐CHD had greater itch at baseline compared to non‐AD CHD (p < 0.01), consequently itch reduction was greater in AD‐subtype. Improvement in QoL (DLQI, Skindex‐Mini) was achieved at 4 weeks maintained to 12 weeks (p < 0.01). No treatment‐related adverse events were reported during the study and no rescue medications were used. Conclusions Ruxolitinib may be a promising treatment for CHD, improving clinical outcomes, itch and QoL. Significant improvement was achieved at 4 weeks and maintained through 12 weeks of treatment.